Socially Responsible Investment and Fiduciary Duty: Putting the Freshfields Report into Perspective - Sandberg, Joakim 1979- (2011)
A critical issue for the future growth and impact of socially responsible investment (SRI) is whether institutional investors are legally permitted to engage in it – in particular whether it is compatible with the fiduciary duties of trustees. An ambitious report from the United Nations Environment Programme’s Finance Initiative (UNEP FI), commonly referred to as the ‘Freshfields report’, has recently given rise to considerable optimism on this issue among proponents of SRI. The present article puts the arguments of the Freshfields report into some further both empirical and critical perspective, however, and suggests that its findings do not call for very much optimism. The general argument is that while the understanding of fiduciary duty outlined by the Freshfields report seems to allow institutional investors to at least sometimes take some social or environmental considerations into account, the support it gives for SRI is notably contingent and, furthermore, it rules out exactly the kind of SRI which proponents of social responsibility and environmental sustainability should hold in highest regard – proactive cases and socially effective investment strategies. If SRI is to become an important force for corporate social responsibility through its adoption by institutional investors, then, it is suggested that legal reform is needed.
Keywords: United Nations Environment Programme Finance Initiative; Socially Responsible Investment; social effectiveness; prudent investor rule; legal reform; Institutional investors; Fresh-fields report; Fiduciary Duty; ethical investment